Behavior of FRP confined UHPFRC-filled steel tube columns under axial compressive loading. (November 2020) - Cao, Shi; Wu, Chengqing; Wang, Weiqiang
Abstract: Ultra-high performance fiber-reinforced concrete (UHPFRC) has been widely investigated in recent years. This study focusses on the experimental results of FRP confined UHPFRC filled steel tube (UHPFRCFST) specimens under axial compression. In total 37 specimens, both square and circular, were prepared and tested to investigate the axial compressive behaviors of FRP confined UHPFRCFST specimens. The main investigated parameters were the FRP layers, the concrete type and the steel fiber addition. The experimental results indicate that axial load capacity of concrete filled steel tube (CFST) specimens can be effectively enhanced by the FRP confinement. However, the performance enhancement was less significant for square UHPFRCFST specimens as compared to circular UHPFRCFST specimens. Comparisons of these results demonstrate that FRP confined CFST specimens exhibit a higher load-bearing capacity in the post-peak stage than the non-wrapped CFST specimens. Moreover, prediction equations were proposed to predict the ultimate axial load capacity of FRP confined UHPFRCFST specimens, and the predicted results matched well with the experimental results. Highlights: The axial compressive behavior of FRP confined UHPFRC-filled steel tube (UHPFRCFST) specimens is investigated. FRP confined UHPFRCFST specimens exhibit higher sudden strength reduction after the peak load. Steel fiber addition can increase the ultimate load for FRP confined UHPFRCFST specimens. Simplified equations are developed to predict the load-bearing capacity of FRP confined UHPFRCFST specimens.